PGM-Free ORR Catalysts Designed by Templating PANI-Type Polymers Containing Functional Groups with High Affinity to Iron. Issue 7 (3rd May 2019) - Yin, Xi; Chung, Hoon T.; Martinez, Ulises; Lin, Ling; Artyushkova, Kateryna; Zelenay, Piotr
Abstract : In this work, a coordination-chemistry approach was used to increase the content of nitrogen-coordinated iron moieties (Fe-Nx ) in platinum group metal-free (PGM-free) catalysts for oxygen reduction reaction (ORR). The catalysts were derived from a series of polyaniline (PANI)-type precursors with N-containing functional side chains having high affinity to iron. The PGM-free ORR catalysts synthesized using such polymeric templates were characterized by scanning electron microscopy, X-ray diffractometry, and tested in an electrochemical cell and H2 -air fuel cell for ORR activity. X-ray photoelectron spectroscopy (XPS) analysis showed that, in spite of similar nitrogen contents, catalysts obtained using PANI-type polymers containing side chains with high affinity to iron had higher Fe content than PANI-derived catalyst. These PGM-free catalysts showed improved ORR activity in an electrochemical cell and in H2 -air fuel cell testing, compared to the PANI-derived catalyst. A correlation between the content of Fe-Nx moieties and the fuel cell performance was observed in these PGM-free ORR catalysts.